Nonlinear adaptive control of semi-active MR damper suspension with uncertainties in model parameters - Yildiz, Ali Suat; Sivrioglu, Selim; Zergeroğlu, Erkan; Cetin, Saban (Springer, 2015)
This paper is concerned with vibration mitigation of a quarter car model using a semi-active magnetorheological (MR) damper. A nonlinear adaptive controller is proposed for vibration attenuation of the quarter car suspension system equipped with MR damper. Proposed adaptive controller can also compensate the uncertainties related to both quarter car model and the MR damper. Moreover, a nonlinear observer is designed to estimate an internal state variable of the MR damper. The mathematical model of the damper which is strongly nonlinear is used to predict the damping force based on velocity input, internal state and voltage input. An experimental test set-up is constructed to validate the MR damper parameters which are adapted by designed controller. Efficiency of adaptive controller is compared with separately designed linear controller and passive cases under bump, sine and C-grade road inputs. The proposed adaptive controller is able to achieve good performance in road holding and driving comfort despite uncertainties in model parameters.
Keywords: Semi-active suspension; MR damper; Adaptive control; Quarter car